Conversations about History, Volume 2 - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About History, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading historians with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Linda Colley, the Shelby M.C. Davis 1958 Professor of History at Princeton University;2. John Elliott, Professor of Modern History at University of Oxford;3. Richard Jan.